Analysis of User Satisfaction of the M-Passport Application Service Using the Technology Acceptance Model (TAM) at TPI Class II Singkawang Immigration Office - Pardi, Pardi (Universitas Padjadjaran, 2024)
This research was based on the adoption of technology in public services related to immigration, namely Passports. Before the existence of M-Passport, passport services were carried out on the spot or by directly arriving at the Immigration Office to submit all administrative requirements. With the adoption of technology in making passports in the form of the M-Passport application, all immigration service requirements can be conducted using the application. The research purpose is to measure the level of satisfaction with the used M-Passport as a form of technology adoption. This type of research is explanatory, which describes the relationship between variables. The data was processed using multiple regression analysis using SPSS series 25 software. The outcomes of the studies indicated that there was an advantageous impact of using M-Passport on user satisfaction as measured by the convenience and usefulness variables, both partially and jointly.